Using telemedicine in nursing homes during the COVID‐19 pandemic: A multi‐perspective view on the implementation process - Petra Plunger; Magdalena Eitenberger; Maria Kletecka‐Pulker; Thomas Wochele‐Thoma; Elisabeth Klager; Ann Kathrin Ruf; Fabian Eibensteiner (Wiley, 2022)
Abstract Aim Centring on nursing homes, we analysed the implementation process of a tablet‐ and videoconferencing‐based telemedicine application from the perspectives of management, nursing staff and physicians. Design We used a qualitative design based on interviews to explore diverse perspectives on the implementation of telemedicine. Methods We conducted fourteen face‐to‐face or online interviews with a purposeful sample of five managers, six nurses and three general practitioners treating residents in Austrian nursing homes during the COVID‐19 pandemic. We condensed data using thematic analysis. Results Nursing home management implemented telemedicine rapidly, using a top‐down approach met with ambivalence by staff. On the part of nurses, their professional understanding of person‐centred care was challenged. Telemedicine also impacted cooperation between nurses and physicians, influencing their respective understanding of their roles. Working experience with digital nursing documentation had a positive effect on users' acceptance of the telemedicine solution.